The Report of the Registration of Titles Commission, 1857 - McDonnell, James (Dublin Statistical Society, 1858)
The present system sacrifices the purchaser and impedes transfers to an unreasonable extent. That proposed by this Report would protect the purchaser at the expense of all other persons, and would shake public confidence in the security of settlements and other derivative interests. I propose a middle course, which would give reasonable security to all parties, and would greatly simplify and facilitate sales, but would not, I admit, make a sale of land as simple as a sale of stock, which is not in my opinion practicable under existing circumstances.
Read Monday, 15th February, 1858
Keywords: Registration of Titles Commission, 1857; 314.15